2017
DOI: 10.1136/bmjstel-2016-000143
|View full text |Cite
|
Sign up to set email alerts
|

Trauma resuscitation: can team behaviours in the prearrival period predict resuscitation performance?

Abstract: BackgroundOptimising team performance is critical in paediatric trauma resuscitation. Previous studies in aviation and surgery link performance to behaviours in the prearrival period.ObjectiveTo determine if patterns of human behaviour in the prearrival period of a simulated trauma resuscitation is predictive of resuscitation performance.DesignTwelve volunteer trauma teams performed in four simulation scenarios in a paediatric hospital. The scenarios were video recorded, transcribed and analysed in 10-second i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 34 publications
(27 reference statements)
3
13
0
Order By: Relevance
“…Third, the finding that coordination patterns discriminate between teams with less versus more experienced members, which is in line with current teamwork research highlighting the importance of patterns,30 has implications for teamwork training as well. Although teamwork is in the focus of most SBT, they typically focus on the quantity and quality of certain behaviours of individual team members.…”
Section: Discussionsupporting
confidence: 83%
“…Third, the finding that coordination patterns discriminate between teams with less versus more experienced members, which is in line with current teamwork research highlighting the importance of patterns,30 has implications for teamwork training as well. Although teamwork is in the focus of most SBT, they typically focus on the quantity and quality of certain behaviours of individual team members.…”
Section: Discussionsupporting
confidence: 83%
“…A planned approach has also been shown to improve crisis resource management . The present study found a positive impact of the planning discussion on crisis resource management scores.…”
Section: Discussionsupporting
confidence: 56%
“…For critical incidents occurring in a medical context there is often a brief period available for planning, for instance immediately before the admission of a known incoming patient. The importance of a free and constructive exchange during this time has been emphasised in a recent non‐randomised paediatric simulation study ; balanced communication structured around pertinent information was associated with better team coordination and a trend towards improved performance. In the present study, planning discussions with a highly situation‐specific content (scenarios with predictable crisis) were associated with an increase of over 11 points (5 + 6) in clinical performance score.…”
Section: Discussionmentioning
confidence: 99%
“…In sum, in complex and ambiguous environments, team information processing cannot be represented merely by the amount of information shared within the team; instead, it is strongly dependent on the extent to which a team collectively engages in higher level processing of the available information. Supported by work on the positive effects of reciprocal communication in hospital trauma teams (Su et al, 2017), we suggest that team processes in which team members engage in an exchange of their interpretations about the situation will lead to positive team outcomes for teams facing a complex, dynamic, and time pressured situation. Therefore, we pose the following research question:…”
Section: Communication Sequences and Information Processingmentioning
confidence: 87%